HxZr3-xPW12O40 as an insoluble and reusable heteropolyacid for highly selective dehydration of fructose to 5-hydroxymethyl fufural in DMSO system - Mulik, Nagesh L.; Niphadkar, Prashant S.; Pandhare, Kiran V.; Bokade, Vijay V. (Chemistryselect, 2018)
Dehydration of fructose is a way to produce an important platform chemical such as 5-hydroxymethylfurfural (HMF) which is widely used to synthesize variety of renewable chemicals and fuel. Heteropoly acid, H3PW12O40 is highly soluble strong acidic catalyst with well-defined structure. This study reports the modification of soluble heteropoly acid to insoluble and reusable heteropolyacid (HxZr3-xPW12O40 ) by exchanging with Zr and investigation of its catalytic performance in selective transformation of renewable fructose to 5-HMF in Dimethyl sulfoxide (DMSO) system. The physico-chemical properties of H(x)Zr(3-x)PW(12)O(40)were derived from Powder-XRD, NH3-TPAD and FT-IR technique. The characterization of HxZr3-xPW12O40 revealed that the Keggin structure of HPA remained intact as proton replaced by Zr. The partial exchange of Zr in H2Zr1PW12O40 catalyst resulted in an increase in acidity, however further increase of Zr above 1, acidity was found to be decreased. At optimized reaction condition, 5-HMF yield of 85% with 100% selectivity was achieved with H1Zr2 PW12O40 catalyst at much lower reaction time of 10 min than reported. The catalyst was observed to be recoverable, reusable as compared to parent H3PW12O40.

Synthesis of ethyl furfuryl ether (potential biofuel) by etherification of furfuryl alcohol with ethanol over heterogenized reusable H1Cs2PW12O40 catalyst - Mulik, Nagesh L.; Niphadkar, Prashant S.; Bokade, Vijay V. (Research on Chemical Intermediates, 2020)
{Ethyl furfuryl ether (EFE) considered as potential biofuel can replace petroleum diesel up to 100%. EFE also has efficient blending properties with biodiesel to improve its cold flow properties. Herein we demonstrate efficient synthesis of EFE by etherification of renewable furfuryl alcohol (FAlc) with ethanol over heterogenized heteropoly acids. Cs-exchanged heterogenized heteropoly acid (H3-xCsxPW12O40
Keywords: B; etherification; Ethyl furfuryl ether; Furfuryl alcohol; H3-xCsxPW12O40; Heterogenized heteropoly acid; L ration